SISTEM INFORMASI PEMESANAN DAN PEMBELIAN OBAT BERBASIS WEB PADA APOTEK PUTRI FARMA BULUKUMBA - Asisa, Wapik; wirawan, Raden; Nur, Muhammad Awal (CV. LAJAGOE PUSTAKA, 2025)
This study aims to: (1) design an information system for ordering and purchasing Web-based drugs at Putri Farma Pharmacy, Bulukumba. (2) To implement an Information System for ordering and purchasing Web-Based drugs at Putri Farma Pharmacy Bulukumba. This study uses the Waterfall research method, where the stages are as follows: Needs analysis, System Design, Coding & Testing, Application and Maintenance. Based on the results of this study, it can be interpreted that: (1) Web-based drug ordering and purchasing information system is designed based on problems that occur in the process of selling drugs in pharmacies, using UML (Unified Modeling Language) including use case diagrams, activity diagrams, class diagrams and sequence diagrams and. The php programming language using the Mysql database as its database storage. (2) The implementation of a web-based drug ordering and purchasing information system at the Putri Farma Bulukumba Pharmacy is well implemented. This can be seen from the results of testing the use of the system using the System Usability Scale (SUS) obtained a score of 81% of 10 respondents with a letter grade of A or very good.